Blended Learning Approach For EFL In-Service Teachers In Constructing Smart Learning Environment: Innovation In Education Personalized For Self-Independent Learning - Nasrullah, Nasrullah; Elsa Rosalina; Alya Shofa Faradila; Raisa Nur Tanziliana; Muhammad Haris Naufal (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
It has been two years since Indonesia and other countries globally went through an abrupt change due to the pandemic covid 19 in educational delivery experiencing online learning to blended learning. To respond to the shift, practitioners and researchers conducted several studies on the implementation and effectiveness of blended learning in many subject areas, especially in the EFL context. However, it is still obscure find out the study which leads to the direct effect of how blended learning can create a smart learning environment as well as spur selfindependent learning. To fill this void, therefore, this study aims at investigating how EFL teachers harness blended learning to create a smart learning environment and self-independent learning for students. To get the data, researchers employed a mix-method approach by using a survey with 18 items and ten items for an open structured questionnaire, then analyzed the data by using descriptive and thematic analysis. The findings of this study reported that EFL Teachers perceived well that in blended learning, not only does the technology used as the instrument deliver materials but it also can be used to accelerate English proficiency by providing a richexposure milieu, cosy interactions and meaningful tasks while learning. In addition, this study implies that EFL teachers should always be inclusive toward the rapid changing of technology and willing to adjust regardless of the learners' diversity and ensure the learning autonomy for learners.